Detection of Antilisterial Activity of 3-Phenyllactic Acid Using Listeria innocua as a Model - Sorrentino, Elena; Tremonte, Patrizio; Succi, Mariantonietta; Iorizzo, Massimo; Pannella, Gianfranco; Lombardi, Silvia Jane; Sturchio, Marina; Coppola, Raffaele (Frontiers in Microbiology, 2018)
The 3-Phenyllactic acid (PLA) produced by various lactic acid bacteria (LAB) possesses a broad spectrum of antimicrobial activity. In this study, the effect of PLA against Listeria innocua was studied with the aim to obtain additional information about its mechanism of action. The effect of pH on the antilisterial activity of PLA was investigated and a pH-dependent behavior, typical of weak acid, was detected. The antilisterial effect of PLA was firstly compared to that produced by lactic acid (LA) and than to that expressed by phenolic acids (gallic, caffeic, and ferulic acids) evaluating minimum inhibitory concentration (MIC), MBC, and survival kinetic parameters. PLA showed MIC values and death kinetic parameters significantly different from those exhibited by LA and by tested phenolic acids. In particular, the MIC value observed for PLA vs L. innocua resulted lower than that of the other preservative compounds studied herein, and consistent with the quantity generally produced by LAB. Moreover, the effect of PLA and phenolic acids on bacterial surface charge and loss of cellular content resulted different. The overall results highlighted strong differences in the antilisterial mechanism of action among PLA and other compounds such as LA and phenols. Specifically, it is possible to hypothesize that the antilisterial mechanism of action due to PLA is associated with the affinity to cell surface, which contributes to the cellular damage.